Pendidikan Kesehatan dan Sosialisasi terhadap persoalan kesehatan Jentik Nyamuk Sejak Dini di Daerah Antang sebagai Tempat Pembuangan Sampah - Hilal, Achmad; Yulis, Dian Meiliani; Latif, Sarifudin Andi; Mainassy, Meillisa Carlen; Nuryati, Anik; Dewi, Chitra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Dengue Hemorrhagic Fever is a contagious disease caused by the Dengue virus and can be transmitted by the bite of the Aedes Aegypti mosquito. It often increases during the rainy season and causes extraordinary events in various regions of Indonesia. School children are at great risk of contracting Dengue Hemorrhagic Fever because they spend more time doing activities at school, both morning and evening. The aim of this community service is to increase knowledge, awareness, attitudes and perceptions of behavior, demonstrate simple skills in action and build healthy living norms and also provide early education to children about caring for mosquito larvae. The method used in this community service activity is through Health Education and Socialization of the health problem of Mosquito Larvae from an Early Age in the Antang Area as a Waste Disposal Site which is directly involved with students in monitoring mosquito larvae. Assistance to students is provided to carry out monitoring of mosquito larvae and increase efforts to eradicate mosquito nests in an effort to control the vector that causes Dengue Hemorrhagic Fever. The result of this activity is that children's knowledge of the process of Dengue Hemorrhagic Fever occurs.